Dispute resolution between the Sunni & the Shiite: Myth or possibility? - Zul Kepli, Mohd Yazid (Ahmad Ibrahim Kulliyyah of Laws (AIKOL), International Islamic University Malaysia, 2017)
The threat of terrorism is not limited to the conflict-zones in the Middle East and North Africa (MENA) region. It has affected many of the world’s most peaceful countries, with terrorist attacks occurring in France, Denmark and Australia. A series of attacks is also recorded in Pakistan, Chad, Tunisia, Kuwait, Kenya, and Yemen. Significant and deadly terrorist attacks also occur in Paris, Brussels, Berlin and Manchester. The ongoing conflicts between the Sunni and the Shia significantly contributed to the conflict. This paper discusses whether effective dispute resolution between the Sunni and the Shia is possible or not. Suggestions and recommendations are also included.